Socialization and Simulation of Learning Style Identification with The Vark Approach for Students and Lecturers - Swarjana, I Ketut; Buntari Agustini, Ni Luh Putu Inca; Suyasa, I Gede Putu Darma; Israfil, Israfil; Tanuparbrungson, Supawan; Indrayani, Ni Luh Dwi; Pangruating Diyu, Ida Ayu Ningrat; Edi Sanjana, I Wayan (Yayasan Ahmad Mansyur Nasirah, 2025)
Learning style is one of the main elements for students and lecturers to determine the right learning support. The VARK (Visual, Aural, Reading, Kinesthetic) approach is one approach that can be used to identify a person's learning style. Unfortunately, not everyone knows this approach to help determine their learning style. The purpose of this community service activity is to socialize and simulate the VARK approach in identifying learning styles. This activity was carried out in May 2024 at Itekes Bali, Denpasar, Indonesia. A total of 52 participants were involved in this activity, consisting of 42 students and 10 lecturers. Participants in this activity came from Itekes Bali, Denpasar, Indonesia, and from Saint Louis College, Bangkok, Thailand. This activity was carried out with the stages of Preparation, Action, Reflection and Evaluation (PARE). The results of the activity showed that most (67%) participants had insufficient knowledge about the VARK approach in identifying learning styles, and all participants (100%) participants succeeded in having good knowledge about the VARK approach in identifying their learning styles after this activity was carried out. The conclusion is that this educational and simulation activity has succeeded in increasing the knowledge of all participants about the VARK approach in identifying learning styles.